The Profile of Romanian Urban Inns - Monica Maria Coroș; Cornelia Pop; Diana-Roua Micu (Tăuțan) (Amfiteatru Economic Journal, 2016)
This paper is the third of a series of studies dedicated to tourist inns on the Romanian market. The previous papers focused on the identification of the tourist inns that currently function on the domestic market. Further, their potential as rural facilities was highlighted and their authenticity was discussed. The relevance of this research is linked to the fact that in the early 1990s tourist inns were excluded from the lists of lodging and food-serving facilities, ceasing to be officially ranked. Consequently, the inns' owners were forced to reclassify as other accepted types or, even worse, to function in the shadow economy , without any official ranking. Moreover, the absence of inns on the market and the incoherent development of certain types of lodgings in Romania, have also led to the fact that entrepreneurs and tourists tend to be confused and, sometimes, not able to differentiate one type of accommodation unit from another. The main purpose of this research is to determine the extent to which urban inns can contribute to the authenticity of the Romanian tourism. From a methodological perspective, the paper relies on both official data (collected and processed based on the official Lists of Hospitality Facilities) and on the information available on specialized websites. Thorough analyses have been run in order to identify the tourist structures pretending to be inns, to further categorize and discuss them according to various criteria. The main findings and conclusions of this paper reveal that inns have the potential to contribute to the authenticity of Romania's hospitality industry .
Keywords: C46; L83; Z32; 330; tourist inns; officially ranked facilities; differentiation; online presence; urban inns; Transylvania; Romania